Large positive correlation between the effective electron mass and the multipolar fluctuation in the heavy-fermion metal Ce1−xLaxB6. Issue 1 (December 2017) - Jang, Dongjin; Portnichenko, Pavlo; Cameron, Alistair; Friemel, Gerd; Dukhnenko, Anatoliy; Shitsevalova, Natalya; Filipov, Volodymyr; Schneidewind, Astrid; Ivanov, Alexandre; Inosov, Dmytro; Brando, Manuel
Abstract For the last few decades, researchers have been intrigued by multipolar ordering phenomena and related quantum phase transitions in heavy-fermion Kondo systems. However, a criticality induced by substitution level (x ), temperature (T ), or magnetic field (B ) is poorly understood even in the prototypical material, Ce1−x Lax B6, despite a large collection of experimental results is available. In this work, we presentT –B, x –T, andx –B phase diagrams of Ce1−x Lax B6 (B || [110]). These are completed by investigating heat capacity, magnetocaloric effect (MCE), and elastic neutron scattering. A drastic increase of the Sommerfeld coefficientγ 0, which is estimated from the heat capacity down to 0.05 K, is observed with increasingx . The preciseT –B phase diagram including a high-entropy region is derived from the MCE analysis in which a knowledge beyond the equilibrium thermodynamics is involved. Finally, thex –B phase diagram atT  = 0, which supports the existence of a quantum critical point atx  > 0.75, is obtained by the same analysis. A detailed interpretation of phase diagrams strongly indicates positive correlation between the fluctuating multipoles and the effective electron mass. Phase diagrams: new features in heavy-fermion materials Thorough measurements of the phase diagrams of Ce1−x Lax B6 shed new light on the phases and properties of heavy-fermion materials. Heavy-fermion systems, in which the electrons have effective masses much higher than the mass of free electrons, exhibit different phases that can be accessed by varying the temperature (T ), applied magnetic field (B ) or amount of lanthanum (x ). Scientists at Max Planck Institute for Chemical Physics of Solids and Technical University of Dresden have completed theT -B, x -T andx -B phase diagrams of the heavy-fermion material Ce1−x Lax B6 revealing, among other features, a new high-entropy phase and a strong correlation between multipolar fluctuations and the effective electron mass. This correlation is expected to be universal in this type of systems, thus the results should hold for other heavy-fermion materials.